Cellini, Vasari, and the Marvels of Malady - Barolsky, Paul (The sixteenth century journal, 1993)
When we think of the maraviglie of the sixteenth century, we usually recall exotic objects, rare animals, flora and fauna, or highly wrought works of art. Such marvels were also given form during or after illness, when the mind, working its wonders, entered the realm of the fantastic. Particularly notable is Cellini's fever-dream in which the artist is pursued by Charon, as if in Dante's hell. Another marvel of malady is found in a letter from Vasari in which he speaks of a drawing made during an illness in order to regain his health. Described in detail, the drawing, now lost, was a satire, a delightful grotesque. Vasari's account and Cellini's vision show us that art can play an imaginative role in illness, as either symptom or therapy, reminding us of the deeper function of all art, which, in various degrees, is restorative and revivifying.